Certificação ambiental e desenvolvimento sustentável: avaliação para o setor sucroalcooleiro localizado na bacia hidrográfica do rio Mogi-Guaçi/SP. - Rodrigues, Isabel Cristina (2004)
The sugar cane culture always was been associated, throughout its history, with ambient degradation and social contingencies. The positioning, on the part of the sugar cane industry, with relation to the negative impacts of its activity on the environment has been defensive, limited to fulfill the legal impositions. In this context, calls the attention the initiative of some sugar cane plants that had decided to produce certified sugar cane and certified organic sugar. This work discusses the motivations that had taken these plants to adopt this system of production and the factors that had concurred for this decision. It starts from the hypothesis that the basic motivation for this decision was the search for a differentiated product, with characteristics valued for the market, and, therefore, apt to increase the profit tax and valuing the capital. The work also allows analyzing until with point the premises of the Sustainable Development are observed by the plants when of its decisions of investments. From of the definition of that the sustainable development must incorporate the regional questions, the sugar cane industry in the Hydrographic Basin of the river Mogi-Guaçu was chosen for the study, because it is in this basin that is found the biggest productive portion of this sector in the country. The research carried through in one of the productive units in the Basin allowed to the construction of a diagnosis of the activity in the regional clipping and a delineation of the necessary changes to the organic production. The resultant diagnosis of the field research allowed concluding that the environment conditions of the plants that had opted to the organic production are significantly improved, but the premises foreseen by the organic certification are incapable to contemplate all the social and environment problems of this activity. The main problems are associated to the extensive exploration of the agricultural activity and the questions of exclusion of workers and small suppliers, generating social problems in the region of the enterprise. The analysis of the plants that had opted to the conversion demonstrates different strategies between them, but the research points out that the motivation that had taken them to decide for the conversion, was directed by the search for a differentiated product. The work concludes that the tools of ambient regulation, based in the market demand, as it is the case of the certificates and labels, is insufficient to contemplate all the premises of the regional sustainable development and that still it becomes necessary the performance of the State and its agencies in the regulation of the access, use and of the occupation of the agricultural space.